Electrochemical Synthesis of Large Area Two‐Dimensional Metal–Organic Framework Films on Copper Anodes. Issue 6 (10th December 2020) - Liu, Youxing; Wei, Yanan; Liu, Minghui; Bai, Yichao; Wang, Xinyu; Shang, Shengcong; Chen, Jianyi; Liu, Yunqi
Abstract: Owing to their excellent physical and electrical properties, metal–organic framework (MOF) materials with well‐defined supramolecular structures have received extensive research attention. However, the fabrication of large‐area two‐dimensional (2D) MOF films is still a significant challenge. Herein, we propose a novel electrochemical (EC) synthesis method for the preparation of large‐area Cu3 (HHTP)2 MOF film on single‐crystal Cu (100) anode. The surface reaction was achieved via charge‐induced molecular assembly. The synthesized MOF film exhibited a high crystalline quality with an electrical conductivity of approximately 0.087 S cm −1, which was around 1000 times larger than the previously reported values for the same material prepared by the interface method. In addition, Cu2 (MTCP), Cu3 (BTPA)2, and Cu3 (TPTC)2 MOF films were synthesized on Cu foil with the same strategy, which confirmed the universality of the proposed method. This controllable EC method can be effectively applied to the industrial‐scale production of 2D MOF films on Cu foil. Abstract : A controllable electrochemical synthesis method of MOF films is developed, and opens the door to the fabrication of large‐scale 2D MOF films. Industrial‐scale continuous production of large‐scale MOF films may be realized via this technology, which can promote their application in the field of microelectronic devices.